Holy scripture and the meanings of the Eucharist in late medieval England, C. 1370-1430 - Pink, S (2011)
This thesis examines how, in late-medieval England, uses of Scripture and associated written discourses expanded to encompass the sacramental functions hitherto privileged to the bread and wine of the Mass. This process, reflecting the longstanding if implicit importance of scriptural symbolism to the medieval Eucharist, also bears witness to a major cultural shift in this period: the assignment to words of the same powers that had underpinned the function of visual, non-verbal symbols in medieval religion and society. As Chapter Two demonstrates, this process was starkly exposed in John Wyclif’s vision of an English religion centred upon the sacrament of the preached word of Scripture, rather than on the Mass. As Chapter Three shows, this was the vision that Wyclif’s followers sought to realize, even if they may have achieved their aims only within a limited band of followers. However, Wyclif’s vision was powerful precisely because its relevance was not confined to Wycliffites. Chapter Four charts how the same substitution was taking place through the dissemination in English of ‘Scripture’, which, in its broadest sense, encompassed meditations upon depictions of Christ crucified as well as preaching. The greatest danger of Wycliffite thought to the late-medieval Church rested in its potential to increase lay awareness of this process. This threat was reflected in the restrictions placed by the English Church upon lay use of religious writings in the early fifteenth century. Nonetheless, as Chapter Five shows through a reading of one of Wyclif’s sternest critics, Thomas Netter, the eucharistic function of ‘Scripture’ had not disappeared but had to be occluded. This occlusion represents the most significant shift in the eucharistic function of ‘Scripture’ in the fifteenth century, allowing its use to develop further without threatening the Mass. This thesis concludes that the unacknowledged yet increasingly central role of ‘Scripture’ helps to explain why, at the Reformation, a scripturally-based religion seemed so quickly to supplant one to which images had been fundamental.